2016
DOI: 10.1111/mcn.12384
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier use and interruption of exclusive breastfeeding: Systematic review and meta‐analysis

Abstract: Identifying modifiable risk factor for exclusive breastfeeding (EBF) interruption is key for improving child health globally. There is no consensus about the effect of pacifier use on EBF interruption. Thus, the aim of this systematic review was to investigate the association between pacifier use and EBF interruption during the first six month. A search of CINAHL, Scopus, Web of Science, LILACS and Medline; from inception through 30 December 2014 without restriction of language yielded 1,866 publications (PROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0
29

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 96 publications
7
78
0
29
Order By: Relevance
“…A metaanalysis with cohort and cross-sectional studies reported that the use of pacifiers has increased the occurrence of breastfeeding interruption (OR: 2.48; CI95%: 2.16-2.85). 34 The use of the pacifier may be one of the EBF interruption causes, but also a marker of difficulties related to breastfeeding, as well as reducing maternal motivation to breastfeeding. In addition, mothers who have problems with breastfeeding make its use to ease the child.…”
Section: Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…A metaanalysis with cohort and cross-sectional studies reported that the use of pacifiers has increased the occurrence of breastfeeding interruption (OR: 2.48; CI95%: 2.16-2.85). 34 The use of the pacifier may be one of the EBF interruption causes, but also a marker of difficulties related to breastfeeding, as well as reducing maternal motivation to breastfeeding. In addition, mothers who have problems with breastfeeding make its use to ease the child.…”
Section: Variablesmentioning
confidence: 99%
“…In addition, mothers who have problems with breastfeeding make its use to ease the child. 34 It is possible that pacifier use inhibits breastfeeding, sucking reduction may compromise milk production with consequent risk of weaning.…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a pacifier has been reported as an indicator of maternal difficulty in BF management and it signals their willingness to wean (26). The association between pacifier use and duration of AME presents conflicting results, although recent systematic reviews concluded that the use of pacifier associated with the shortest time of AME (27,28).…”
Section: Discussionmentioning
confidence: 99%